2000
DOI: 10.1055/s-2000-100
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Endoscopy - Comparison with Colonoscopy in the Detection of Space-Occupying Lesions of the Colon

Abstract: Virtual colonoscopy is feasible, well tolerated, and capable of detecting most lesions greater than 10 mm in diameter. This technique is continuing to be developed and warrants further evaluation as a diagnostic and screening tool in colorectal neoplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(28 citation statements)
references
References 23 publications
2
26
0
Order By: Relevance
“…We included 47 prospective studies involving 10,546 patients that compared CTC to the reference standard of CC or surgery [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63]. Table 2 shows detailed information from individual studies.…”
Section: Resultsmentioning
confidence: 99%
“…We included 47 prospective studies involving 10,546 patients that compared CTC to the reference standard of CC or surgery [17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63]. Table 2 shows detailed information from individual studies.…”
Section: Resultsmentioning
confidence: 99%
“…Reported clinical series [9][10][11][12] showed encouraging results. Hara et al, in a series of 70 patients, reported a sensitivity of 75% for lesions greater than 10 mm.…”
mentioning
confidence: 94%
“…Advances in computerized tomographic (CT) techniques and the supportive computer software for these devices may soon alter the need for invasive colon screening techniques [8]. CT colonography or virtual colonoscopy has advanced to a point where this may be the optimal initial screening technique for colorectal cancer [11].…”
Section: Discussionmentioning
confidence: 99%